2016
DOI: 10.5606/tgkdc.dergisi.2016.12955
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the measurements of arterial lactate and mixed venous oxygen saturation for the evaluation of tissue perfusion after coronary artery bypass grafting

Abstract: Bu çalışmada koroner arter baypas greftleme sonrasında kan laktat düzeyleri ve miks venöz oksijen satürasyonu arasındaki muhtemel ilişki incelendi. Ça lış mapla nı:Çalışmaya Kasım 2011-Aralık 2012 tarihleri arasında ekstrakorporeal dolaşım ile elektif koroner arter baypas greftleme yapılan toplam 147 erişkin hasta (104 erkek, 43 kadın; ort. yaş 59±11 yıl; dağılım 36-87 yıl) alındı. Ameliyat sonrası 30, 60, 120. ve 240. dakikalarda ve 24. saatte ölçülen arteriyel kan gazı, miks venöz gaz ve hemodinamik parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They also found a high complication rate and long length of ICU stay. However, Okten et al [20] reported that although blood lactate levels provided information on the adequacy of tissue perfusion, changes in lactate levels did not correlate with mixed venous oxygen saturation. Furthermore, Guinot et al [21] stated that ΔPCO 2 was associated weakly with arterial lactate.…”
Section: Discussionmentioning
confidence: 99%
“…They also found a high complication rate and long length of ICU stay. However, Okten et al [20] reported that although blood lactate levels provided information on the adequacy of tissue perfusion, changes in lactate levels did not correlate with mixed venous oxygen saturation. Furthermore, Guinot et al [21] stated that ΔPCO 2 was associated weakly with arterial lactate.…”
Section: Discussionmentioning
confidence: 99%